Non-protein nitrogen determination: A screening tool for nitrogenous compound adulteration of milk powder. (May 2017) - DeVries, Jonathan W.; Greene, George W.; Payne, Anitra; Zbylut, Steven; Scholl, Peter F.; Wehling, Paul; Evers, Jaap M.; Moore, Jeffrey C.
Abstract: Kjeldahl and Dumas crude protein measurement methodologies do not distinguish between nitrogen native to milk and nitrogen in low molecular mass, nitrogen-rich adulterants. Measuring the non-protein nitrogen (NPN) content is one possible means of closing this loophole. Four methods were considered, with three selected for further research and validation: protein precipitation using trichloroacetic acid, protein precipitation using tannic acid, and molecular mass cut-off filtration. Kjeldahl assay was used on the supernatant or filtrate for all three methods. An NPN reference concentration range was established using 15 milk powder samples. This was followed by spiking experiments using seven low-molecular-weight, nitrogen-rich adulterants. Tannic acid precipitation and molecular mass cut-off filtration, both simple techniques available for routine use in food analysis laboratories, proved to be suitable for detecting the adulteration of milk powders with a variety of nitrogenous contaminants. NPN concentrations of ≥0.34% in milk powders are suspected to result from adulteration.